Media Argumentation : dialectic, persuasion and rhetoric - Walton, Douglas N., 1942- (Cambridge, United Kingdom Cambridge University Press, 2007)
Logic, dialectic, and rhetoric -- The speech act of persuasion -- Propaganda -- Appeals to fear and pity -- Ad hominem arguments in political discourse -- Arguments based on popular opinion -- Fallacies and bias in public opinion polling -- Persuasive definitions and public policy -- Arguments -- The structure of media argumentation.
Keywords: Razonamiento; Dialéctica; Medios de comunicación social